HUBUNGAN KEBISINGAN, KELELAHAN KERJA DAN BEBAN KERJA MENTAL TERHADAP STRES KERJA PADA PEKERJA BAGIAN BODY RANGKA PT. X - Johan Amir; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2019)
Stress at work is stimulation from the outside or inside the body which causes adverse effects. Factors that influence include work environment (noise), work fatigue at work and mental workload that reduce performance, efficiency and productivity at work. The purpose of this study is to describe and analyze the correlation of noise, fatigue at work, mental workload to stress at work in PT X Frame Body Parts workers. The noise in the body part is quite high at 82.13 dB to 85.42 dB. This study uses quantitative with analytic observational and cross sectional research design. Population of the subject was 350 workers and the sample of this study was 60 workers. The instrument used in this study are GHQ-12 and NASA-TLX questionnaires to obtain stress at work data and mental workload, noise measurement with Sound Level Meter, and reaction timer application for fatigue at work data. The results of statistical tests with the Rank Spearman found that there was a correlation between mental workload (p = 0.026) and fatigue at work (p = 0.013) with stress at work. There is no correlation between noise (p = 0.878) with stress at work. It is recommended for business owners to supervise the use of earplugs. Workers are advised to take advantage of rest periods as much as possible.